2018
DOI: 10.3892/ijmm.2018.3706
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of microRNA‑23b‑3p contributes to the development of intracranial aneurysms by targeting phosphatase and tensin homolog

Abstract: MicroRNA‑23b‑3p (miR‑23b‑3p) has been reported to be involved in the pathogenesis of a number of diseases, including non‑small cell lung cancer and gastric cancer, by acting on different signaling pathways. The present study aimed to understand the association between the miR‑23b‑3p level of intracranial aneurysms (IAs) and the mechanism involved. Computational analysis was used to search for the target of miR‑23b‑3p, and luciferase assay was used to validate the miRNA/target association. Western blot analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Multiple studies have demonstrated the dysregulation of miRNAs in patients with both IA and aSAH [ 23 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 ] ( Table 1 ). However, it is essential to note that the quality of evidence in most of these studies is generally low.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple studies have demonstrated the dysregulation of miRNAs in patients with both IA and aSAH [ 23 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 ] ( Table 1 ). However, it is essential to note that the quality of evidence in most of these studies is generally low.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, miR-23b-3p has been specifically linked to various functions in various cancers through a cell-type-specific manner. In various kinds of tumors, miR-23b-3p was reported to act as a tumor suppressor [ 34 , 35 ]. In this study, miR-23b-3p expression level was markedly reduced in COAD tissues compared with adjacent normal colonic tissues and significantly downregulated in all four COAD cell lines (SW620, SW1116, CW-2, and LoVo) analyzed relative to its expression in a normal colonic epithelial cell NCM460.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the levels of several miRNAs (e.g., miR-143, miR-145, and miR-23b) were found to be consistently down-regulated among the studies described above [30,45,47,54]. For example, miR-23b was reduced in IA tissues and was reported to target phosphatase and tensin homolog (PTEN) [55], a key regulator of proliferation, differentiation, and cytokine production during pathological vascular remodeling in smooth muscle cells [56]. MiR-143 and miR-145 play an important role in controlling vascular smooth muscle phenotype by maintaining or inhibiting differentiation [28,57] and were found to be significantly down-regulated in IA tissues and plasma [30,44,45,47,54,57].…”
Section: Mirna In Intracranial Aneurysmal (Ia) Tissue and Subarachnoid Hemorrhagementioning
confidence: 95%